A Review on Techniques and Challenges in the Harvest of Mesopelagics - Remesan, M. P. (Fishery Technology, 2019)
Harvesting of underutilized mesopelagic resources is among the possible solutions to increase capture fish production, which will also facilitate recovery of overexploited fish resources. Mesopelagics can be a source for fish meal, which is in great demand from the growing aquaculture and animal feed industry and will find applications in areas like nutraceutical and cosmetic industries. Recent estimates based on acoustic data, put the biomass of mesopelagic fishes between 11,000 and 15,000 million tonnes in the world oceans. Even though there is a large potential for developing a fishery for mesopelagics, very little information is available on the appropriate commercial harvesting systems. About 75% of total global catch of small mesopelagic fishes is accounted by myctophids. Average world annual production of myctophids between 1970 and 2015 has been 10,640 tonnes, with a maximum of 74,751 tonnes in 1990. Aimed midwater trawling and pair trawling with appropriate trawl designs have been considered suitable for harvesting mesopelagic resources. An overview of the study is the mesopelagics in the Indian Ocean and its availability in the deep sea shrimp trawl bycatch. Sampling gears and commercial fishing techniques targetingÂ mesopelagics are discussed along with details of experimental aimed midwater trawling conducted in Arabian Sea, targeting mesopelagic resources.